Teaching The Impact of Online Learning and Early Art Practice on Emergent Writing Skills in Egyptian Preschoolers - Mustafa, Amira; Syamsudin, Amir (JURNAL PENDIDIKAN USIA DINI, 2025)
This study investigates the emergent writing skills of Egyptian preschoolers within an online learning environment and explores parents' perceptions of early art practices' influence on these skills. While foundational fine motor and pre-writing activities are crucial for literacy development, specific research examining their impact in online contexts and parental views, particularly in Egypt, remains limited. This research addresses three primary questions: What is the level of emergent writing skills (including letter formation, word attempts, and drawing of pictures) among Egyptian preschoolers in an online learning environment? What are Egyptian parents' perceptions regarding their children's engagement in early art practices (such as drawing and colouring) and its influence on their emergent writing skills within the context of online learning? And what is the observed relationship between parents reported early art practices (drawing and colouring) and the demonstrated emergent writing skills in Egyptian preschoolers' writing samples within an online learning environment? A qualitative descriptive approach was adopted, utilizing a parental survey and analysis of children's writing samples from ten Egyptian preschoolers (P01-P10) engaged in online learning. The parental survey assessed home environment, art practice engagement, and parental perceptions. Children's writing samples were analyzed for various emergent writing indicators, including pre-writing strokes, letter attempts, word formation, and drawing quality. Findings reveal a varied but generally developing level of emergent writing skills among the preschoolers, with a strong correlation observed between consistent early art engagement reported by parents and more advanced emergent writing indicators in children's samples. Parents largely perceive early art practices as highly beneficial for fine motor development and emergent literacy, emphasizing improved pencil grip, hand-eye coordination, and confidence. This study highlights the critical role of early art practices and parental involvement in supporting emergent writing skills, even within online learning settings. Recommendations include integrating structured art activities into online curricula and empowering parents with resources to facilitate pre-writing development at home. Further research is needed to explore longitudinal impacts and diverse online learning models.